Management of Iodine Contrast Media Related Anaphylactic Shock following Renal Arteriography: A Rare Case Report - Kino, Kino; Karmia, Rofila Dita; Harun, Harnavi (Sciences of Pharmacy, 2026)
Background, anaphylactic shock (AS) caused by iodinated contrast media (ICM) is a rare but potentially life-threatening immediate hypersensitivity reaction. Despite widespread use of ICM in diagnostic imaging, data on ICM-related AS are limited, particularly in Indonesia. Early recognition and timely intervention are crucial to reduce morbidity and mortality. Case presentation, a 28-year-old female underwent renal arteriography with iodixanol. Within 5 minutes of contrast administration, she developed a generalized pruritic rash, dyspnea, vomiting, hypotension, and unstable cardiac parameters. Clinical presentation confirmed iodixanol-induced anaphylactic shock. Management, initial management included intramuscular epinephrine, rapid intravenous fluids, intravenous antihistamines and corticosteroids, and norepinephrine infusion. The patient’s hemodynamic status stabilized, and she was monitored in the CVCU for 48 hours. Outcome and conclusion, the patient recovered fully without complications. This case emphasizes the importance of rapid recognition and prompt pharmacologic intervention in ICM-induced anaphylaxis, while highlighting the value of thorough allergy documentation and preventive counseling.